Dal latino al volgare. Echi catulliani nei “Rerum Vulgarium Fragmenta” - Donatella Nisi (Parole Rubate, 2019)
This paper examines the presence of Catullo’s Liber in Petrarch poems, through the recognition of various references scattered throughout his Rerum Vulgarium Fragmenta with the use of the humanistic imitatio technique. Therefore, additional tiles are introduced into the mosaic of the Catullian echoes, which were already acknowledged by previous commentators.